Development of Pronunciation Textbooks Based on Communicative Language Teaching Approach - Aboe, Roswita M.; Bahara, Susana R. (STKIP Yapis Dompu, 2022)
Research has found out that speaking skill covered pronunciation as the fundamental significance in linguistic proficiency. Surprisingly, in most English Language test, pronunciation appears to be the subject that is often neglected. Despite the generous amount of media utilize to practice utterance of English syllable or words, the supply of pronunciation teaching textbook source is scarce. By employing research and development (R&D) of 4D design, this study aimed at describing the model, validity and reliability of the Pronunciation textbook for English Education students. This research involved 38 students and 2 (two) experts’ rater to examine the book based on BSNP (Badan Standar Nasional Pendidikan or National Education Standard Agency) criteria. The result pointed out, that the model of pronunciation book corresponded with the KKNI standard curriculum and based on BSNP Criteria. The questionnaires validation result from respondent showed that rxy is 0.64 with the category of valid, and the reliability test result from Cronbach Alfa showed that r11 is 1.04 in the level of ?1.00 with the category of very high reliability. The validity and reliability of the product were also verified by two experts’ rater and analyzed by using Aiken index technique. In this analysis, the V index showed the value of 0.91 with the category of very high (from the scale of 0.8-1.00) for the content eligibility, presentation, language and graphic. Accordingly, Pronunciation textbooks model developed based on communicative language teaching approach is valid and reliable.